Impact of society for social service credit on poor women of Mymensingh district in Bangladesh - Alam, Md Ashraful; Islam, Syful; Toma, Nowrin Islam; Islam, Md Shofiqul (Asian-Australasian Journal of Food Safety and Security, 2019)
The present study is an attempt to assess the impact of SSS (Society for Social Service) credit on women beneficiaries of Gouripur upazila at Mymensingh district in Bangladesh. The study revealed that both annual income and expenditure of the respondent households have increased after joining the micro credit program of SSS. Average family size of agriculture and petty business enterprises were 4.69 and 4.21. Average annual income of agriculture and petty business enterprises were Tk 80726.57 and 74864.14 respectively while average annual expenditure of agriculture and petty business enterprises were Tk 78776.65 and 67912.37 respectively. It was evident in the case of children education (60.00 percent), labor employment (40.00 percent), crop production (55.00 percent), taking care of children (30.00 percent) and rearing poultry birds. The highest (66.67 percent) proportion of the respondents reported insufficiency of credit supply was a moderate problem and only 33.33 percent of them reported this not at all a problem to them. The interest rate charged by the SSS as a major problem, 36.67 percent of the respondents opined as high. About 48.49 percent of the respondents reported that burden of old debt was not at all a problem while 1.67 percent said that it was a great problem to continue their existing activities. The finding shows that SSS credit program encouraged the women beneficiaries to participate in the social development activities in the study area. Asian Australas. J. Food Saf. Secur. 2019, 3(2), 53-62